Body mass estimates of the earliest possible hominins and implications for the last common ancestor. Issue 122 (September 2018) - Grabowski, Mark; Hatala, Kevin G.; Jungers, William L.
Abstract: Many hypotheses regarding the paleobiology of the earliest possible hominins, Orrorin tugenensis and Ardipithecus ramidus, are dependent upon accurate body mass estimates for these taxa. While we have previously published body mass predictions for Orrorin and Ardipithecus, the accuracies of those estimates depend on the assumption that the postcranial skeletal dimensions and body masses of these taxa followed scaling patterns that were similar to those observed in modern humans. This assumption may not be correct because certain aspects of postcranial morphology in Orrorin and Ardipithecus differ from modern humans, and suggest that their overall body plans might be unique but more similar to modern non-human great apes than to modern humans. Here we present individual body mass predictions for O. tugenensis and Ar. ramidus assuming that they followed postcranial scaling patterns similar to those of chimpanzees. All estimates include individual prediction intervals as measures of uncertainty. In addition, we provide equations for predicting body mass from univariate postcranial measurements based on the largest sample ( n  = 25) yet compiled of common chimpanzee skeletons with known body masses, which is vital for calculating prediction intervals for individual fossils. Our results show that estimated body masses in Orrorin and Ardipithecus are generally larger when derived from a chimpanzee-like scaling pattern compared to estimates that assume a human-like pattern, though the prediction intervals of the two sets of estimates overlap. In addition, the more complete of the two known Orrorin femora has an overall scaling pattern that is more similar to common chimpanzees than to modern humans, supporting the application of a non-human great ape comparative model. Our new estimates fall near the male ( Ardipithecus ) average and in between the male and female averages ( Orrorin) for wild-caught common chimpanzees. If a chimpanzee-like pattern of scaling between postcranial dimensions and body mass did exist in these earliest hominins, our results suggest the large body masses found in some early australopiths were already present in taxa near the origins of our lineage, and perhaps also in the Pan - Homo last common ancestor.